Some aspects of the age characteristics of the sensory-cognitive development of the child during the preparation of future educators - Bakay, S. (New Collegium, 2023)
The article is devoted to the study and disclosure of age-related features of sensory-developmental development of preschool child, in particular early age during the preparation of applicants of the second (master’s) level of higher education for further practical activities of preschool teachers. It is noted that the educational direction "Child in the sensory-cognitive space" orients teachers to form sensory-cognitive, logical-mathematical and research competences in children, which should be considered as one holistic integrated competence. A significant contribution of outstanding teachers of previous years to the problems of sensory-cognitive space of preschool children has been highlighted and characterized. Based on the analysis of modern psychological and pedagogical sources and scientific articles of specialists on this topic, the importance of sensory development for a preschool child is analyzed, the gradual sensory development of an early childhood child is indicated, and important aspects of subject and cognitive activity are emphasized. It is proved that the main goal is to teach the child: to perceive and distinguish the shape, size, color of the object through visual, touch and motor examination; to form an idea of the different properties of objects, comparing them with each other; encourage tasks with adults; to practice in establishing similarities and differences between objects; familiarize with geometric shapes: circle, square, triangle, ball; learn to recognize familiar geometric shapes in an environmental object; familiarize with the size and properties of objects; familiarize with colors, form the ability to recognize familiar colors in the environment, find pairs of objects of the same colors, group objects by color; to form the ability to distinguish objects with the help of tactile sensations; develop olfactory and taste sensations; develop auditory sensations, teach to distinguish between quiet and loud speech, music, birdsong, animal sounds, etc.